Effects of chronic low-frequency pulsed magnetic fields exposure on the contractility and morphology of biceps brachii in healthy adults–a randomized controlled, double-blind trial - Li, Zhongshan; Li, Wenhao; Bai, Shi; Yang, Tieli (Frontiers in Medicine, 2025)
BackgroundLow-frequency pulse magnetic fields (PEMF) has been proven by classic transient receptor potential channel 1 (TRPC 1) transcription activation peroxisome proliferator-activated receptor-γ coactivator-1α (PGC-1α) increase upstream of the mitochondria calcium - axis to increase muscle and mitochondria function, and recreates the consistent with exercise induced metabolic adaptations and power to ascend.MethodsEighty healthy subjects with a mean age of 20 years were recruited and randomly divided into a PEMF group receiving magnetic field stimulation and a control group receiving sham treatment, with 40 patients in each group. The trial lasted for 4 weeks. Both groups were subjected to either a 15 min magnetic stimulation intervention or a sham treatment every 48 h. B-mode ultrasound images were used to evaluate changes in muscle thickness, cross-sectional area, pennation angle, and stiffness.ResultsThe PEMF group showed a significant increase in the MVC (maximum voluntary contraction) value and a significantly higher amplitude of the increase than the control group. There was no significant difference in BMI (Body Mass Index) between the two groups before and after the trial, nor in the rate of change in BMI between the two groups. However, from the analysis of the change trends, the PEMF group showed a downward trend, while the control group showed an increasing trend. In the PEMF group, all four parameters of muscle morphology were significantly higher than pre-test, while in the control group, all but one of the muscle stiffness metrics were significantly lower. The PEMF group had significantly higher muscle morphological parameters than did the control group.ConclusionThe current clinical trial showed that in healthy individuals aged 20 years, after 4 weeks of chronic exposure to a low-frequency pulsed magnetic field (1.5 mT, 3,300 Hz), the maximum voluntary contraction force of the biceps brachii muscle was significantly increased, and a contralateral effect was observed. At the same time, the muscle thickness, cross-sectional area, pennation, and stiffness of the intervention arm increased significantly. It provides a supportive basis for the improvement of muscle histopathology using this technique as an exercise replacement and a medical strategy for muscle improvement.Clinical trial registration[https://www.chictr.org.cn], identifier: [ChiCTR2300078947].